-6(-4x+3)=-1+7x

Simple and best practice solution for -6(-4x+3)=-1+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-4x+3)=-1+7x equation:



-6(-4x+3)=-1+7x
We move all terms to the left:
-6(-4x+3)-(-1+7x)=0
We add all the numbers together, and all the variables
-6(-4x+3)-(7x-1)=0
We multiply parentheses
24x-(7x-1)-18=0
We get rid of parentheses
24x-7x+1-18=0
We add all the numbers together, and all the variables
17x-17=0
We move all terms containing x to the left, all other terms to the right
17x=17
x=17/17
x=1

See similar equations:

| 15+(x+6)=9 | | s/14=0.5 | | 4(x+5)=8x+20-2x | | w/4-17=9 | | x-1+2=4 | | 1/2(x-4)=-2x+6 | | 5x+6=$ | | 6x-8=-2x-16 | | 7v+5v=-2+5v+2+7v | | 3-4v=1- | | (-4x+1=21) | | 10h=8h+24 | | |-6+2n|=18 | | 2x85+9.4=21 | | 14=x/5+9 | | 6(n+4)-4=44 | | -24+12y=48 | | (4-3x)-(-x+1)=4x-3 | | 1/5x+1/3=1/4 | | 3(u-6)-6u=12 | | 4f-15=3f-23 | | -43-6b=-6(b=6) | | 6+8(8-6x)=-3x+5(5-6x) | | (-6x=18) | | -2x+12=-10x+18 | | y=2.93=36 | | 3–4v=11 | | 2(5x-2)+4x=2(x-20) | | 1+3x=-15+8x-3x | | 9-t=9-7t | | 2(2x+2)-5x=5-6(x-4) | | 1/3-2/3m=2/3m+2/3 |

Equations solver categories